Manganese Peroxidase, Produced by Trametes versicolor during Pulp Bleaching, Demethylates and Delignifies Kraft Pulp - Paice, M. G. (1993)
Previous work has shown that Trametes (Coriolus) versicolor bleaches kraft pulp brownstock with the concomitant release of methanol. In this work, the fungus is shown to produce both laccase and manganese peroxidase (MnP) but not lignin peroxidase during pulp bleaching. MnP production was enhanced by the presence of pulp and/or Mn(II) ions. The maximum level of secreted MnP was coincident with the maximum rate of fungal bleaching. Culture filtrates isolated from bleaching cultures produced Mn(II)- and hydrogen peroxide-dependent pulp demethylation and delignification. Laccase and MnP were separated by ion-exchange chromatography. Purified MnP alone produced most of the demethylation and delignification exhibited by the culture filtrates. On the basis of the methanol released and the total and phenolic methoxyl contents of the pulp, it appears that MnP shows a preference for the oxidation of phenolic lignin substructures. The extensive increase in brightness observed in the fungus-treated pulp was not found with MnP alone. Therefore, either the MnP effect must be optimized or other enzymes or compounds from the fungus are also required for brightening.